Recognizing Immunoglobulin G4-Related Overlap Syndromes in Patients with Pancreatic and Hepatobiliary Diseases - Aldo J Montano-Loza; Eoin Lalor; Andrew L Mason (Canadian Journal of Gastroenterology)
The first description of autoimmune pancreatitis and elevated serum immunoglobulin-G4 (IgG4) in 2001 heralded further reports of several related autoimmune diseases with raised IgG4 levels. It is now recognized that a spectrum of overlap syndromes associated with increased IgG4 and biopsy evidence of IgG4-producing plasma cells, which has now been convincingly linked with cholangitis, autoimmune hepatitis, Sjögren’s syndrome, nephritis and retroperitoneal fibrosis. Collectively, this disease cluster is referred to as IgG4-related systemic disease. The importance of making the correct diagnosis is underscored by the management of individuals with IgG4-related systemic disease. In the first instance, patients generally have a dramatic response to immunosuppressive therapy, whereas patients with other forms of cholangitis and pancreatitis do not. Also, surgical management of pancreatic malignancy can be avoided once the correct diagnosis of IgG4-related disease has been made. In the present review, an overview of the current information regarding the role of IgG4 and IgG4-positive cells affecting the biliary system, pancreas and liver is provided.